Prognostic factors for survival in pancreatic cancer patients received radiotherapy: a single-center experience - ALKIŞ, HİLAL (My University, 2023)
Aim: To investigate survival outcomes and factors affecting the prognosis of patients with pancreatic cancer (PC) who received radiotherapy (RT). Material and Method: A total of 73 patients with PC who received RT between 2013 and 2021 were included in the study. Clinical, demographic, and histopathological features of the patients, and the goal of RT (adjuvant, definitive, neoadjuvant, or palliative) were recorded. Results: Median age of the patients was 62 (37-78). Male to female ratio was 1.6. In patients treated with adjuvant (n=52), definitive (n=13), and palliative (n=7) RT, median overall survival (OS) was 25.7 (11.6-39.7), 16 (7-67), and 9 (5-52) months, respectively. Survival time of 1 patient who received neoadjuvant RT was 26.6 months. Lymph node ratio (LNR) was significantly associated with OS. Patients with LNR ≤0.4 had better survival compared to those with LNR >0.4 (p=0.003). Furthermore, patients with LNR ≤0.4 and received adjuvant RT survived longer than the rest of the patients (12.1 vs. 7.7 months, p=0.001). Larger tumors (p=0.04) and LNR (p=0.003) were associated with poorer survival in univariate analysis, however, in the multivariate analysis, OS was found significantly affected only by LNR (p=0.01). Other factors were not found associated with survival. Conclusion: LNR had a strong correlation with OS in PC patients treated with radiation. Smaller LNR was associated with better survival in patients who received RT in the adjuvant setting.
Keywords: Pancreatic cancer; prognostic factors; survival; radiotherapy